Overview of the Analytical Method Development for Ertugliflozin Using UV and HPLC Techniques - Priyanka Kedar,; Dr.Vinayak Gaware, (Asian Journal of Pharmaceutical Research and Development, 2025)
Ertugliflozin is a new sodium-glucose cotransporter 2 (SGLT2) inhibitor used to treat type 2 diabetes. Because of its extensive use, it is critical to develop precise and reliable analytical methods for determining its presence in pharmaceutical formulations and biological materials. Several analytical methods have been developed to determine ertugliflozin, including UV spectroscopy, HPLC, and LC-MS/MS. Ertugliflozin has been measured using UV spectroscopy in pharmaceutical formulations and HPLC in biological samples. LC-MS/MS has been used for the determination of ertugliflozin in biological samples, providing high sensitivity and specificity. The analytical method development for ertugliflozin involves several steps, including method validation, optimization of chromatographic conditions, and selection of suitable detectors. Method validation involves evaluating the accuracy, precision, specificity, and robustness of the analytical method. Optimization of chromatographic conditions involves selecting suitable columns, mobile phases, and detection wavelengths. Selection of suitable detectors involves choosing detectors that provide high sensitivity and specificity. This review provides an overview of the analytical method development for ertugliflozin using UV and HPLC techniques. The review highlights the importance of method validation, optimization of chromatographic conditions, and selection of suitable detectors in analytical method development. UV and HPLC techniques have been widely used for the determination of ertugliflozin, providing high sensitivity and specificity. This review provides an overview of the analytical method development for ertugliflozin using UV and HPLC techniques, highlighting the importance of method validation, optimization of chromatographic conditions, and selection of suitable detectors.